A Survey on the Frequency of Medication Errors Caused Due to Look-Alike Drugs in the Emergency Department of the Educational Hospitals of Shiraz, Iran, 2016 - Syedeh Zohreh Mosakazemi; Peivand Bastani; Milad Ahmadi Marzaleh; Mahmoud Reza Peyravi (Iranian Journal of Health, Safety and Environment, 2019)
The words "look-alike" and "sound-alike" are used to express the confusion caused by drugs whose names or features are similar. Look-alike/sound-alike (LASA) drugs are one of the most common causes of medication errors. The emergency department is the first place where mistakes related to LASA drugs occur. Medicinal errors increase health care costs by about two billion dollars annually. This study examines the frequency of errors resulting from LASA drugs in the emergency department and identifies the main causes of these errors. This sectional analytical study was conducted in 2016 in the Namazi and Faghihi hospitals of Shiraz. The questionnaire was developed by the researcher and its validity was confirmed by the experts. The stratified sampling method was used and the sample size was determined to be 106 people, based on the Cochran formula. The data were analyzed using the software SPSS 20 by the Pearson correlation coefficient, the independent t-test, and an analysis of variance (ANOVA). Seventy-seven nurses stated that during the past six months they had made at least one error resulting from look-alike medication and a total of 132 errors were reported. The most common errors in medication related to ampoules and vials. The rate of errors was statistically significant in terms of marital status (p